Nutrient composition of foods to accompany nutrition science and applications - Smolin, Lori A.; Grosvenor, Mary B. (John Wiley & Sons, 2008)
Obesity has become a major health issue throughout the world, but many people just aren't aware of the proper nutrition needed in a diet. Smolin guides readers through the science of nutrition, providing real-world examples to show them how to apply this information to their lives. Each chapter delves into the strong science base while exploring the basis of current nutrition recommendations. This approach will help readers effectively evaluate new information that they encounter.